The protective effect of a satisfying romantic relationship on women's body image after breast cancer: a longitudinal study. Issue 6 (4th September 2016) - Cairo Notari, Sarah; Notari, Luca; Favez, Nicolas; Delaloye, Jean‐François; Ghisletta, Paolo
Abstract: Objective: To examine the protective role of relationship satisfaction on body image in women with breast cancer throughout the first year post‐surgery. Methods: Seventy‐four Swiss patients engaged in a relationship filled out a questionnaire assessing body image disturbance 2 weeks, 3 months, and 1 year after surgery. A univariate latent change score model was used to analyze the evolution of body image disturbance and the contribution of relationship satisfaction to body image disturbance. Results: Women who were satisfied with their relationship reported less body image disturbance than did dissatisfied women at 2 weeks post‐surgery. Being married was also associated with less body image disturbance at that time. The protective effect of these relational variables was still observable 1 year later. Changes in body image disturbance over time were explained by the negative impacts of mastectomy and chemotherapy. Conclusions: How women perceive the impact of breast cancer treatment on their body may be partly determined by the quality of the relational context in which they live.